Technology & Innovation in South Africa: Unlocking the Future through AI, Blockchain, and Quantum Computing - Magasa, Lynnette Nontobeko (Global journal of Business and Integral Security, 2026)
South Africa will continue to exist at the convergence of the digital revolution and the green economy, facing persistent challenges such as sluggish economic growth, high unemployment, and an entrenched digital divide. This study will introduce the Integrated Emerging Technologies Framework (IETF), which will amalgamate Artificial Intelligence (AI), Blockchain, and Quantum Computing to promote equitable growth. Case examples from the Council for Scientific and Industrial Research (CSIR), the South African Reserve Bank’s (SARB) Project Khokha, and the Wits–IBM Quantum Partnership will illustrate how these technologies improve productivity, transparency, and resilience. The research will employ a mixed-method, desk-based approach to assess adoption patterns, GDP contributions, and policy barriers. The research findings will advocate cohesive policies, investments, and research efforts aimed at transforming systemic difficulties into opportunities. This framework seeks to align South Africa's innovation trajectory with the Sustainable Development Goals (SDGs) and the National Development Plan (NDP) 2030.